Unit-linked life insurances as a form of protection for the future - Magdalena Homa (Economic and Environmental Studies (E&ES), 2017)
Insurances with capital funds (unit-linked, UFK), i.e. life and annuity saving and covering insurances combined with shares in selected investment funds of financial institutions are considered as additional form of pension saving. However, they are frequently seen as uneconomical products, which is caused mainly by the fact that insurance policies compensations does not live up to expectations of the insured. It became an impulse to implement the analysis of cash flow characteristic of such insurance types, carry out an accurate valuation of the unit-linked insurance portfolio, as well as to investigate financial surplus in relation to a traditional insurance with guaranteed sum.
Keywords: C58; G22; G17; 330; unit-linked insurance; European option; valuation; value of insurance; Monte-Carlo method